Analisis Penerapan SAK ETAP Pada Laporan Keuangan Koperasi Simpan Pinjam XYZ Di Cikarang: Analysis of the Implementation of SAK ETAP in the Financial Statements of XYZ Savings and Loan Cooperatives in Cikarang - Alawi, Tassyah; Nuraliza, Della; Riska, Ai Nurul; Alimnaesti, Eka (CV Warnak Johanna Nusantara, 2026)
Transparent and accountable financial statements are key to maintaining the trust of cooperative members. This study aims to analyze and evaluate the implementation of Financial Accounting Standards for Entities Without Public Accountability (SAK ETAP) in the preparation of the financial statements of XYZ Savings and Loan Cooperative for the period ending December 31, 2023. The research method used is qualitative with a descriptive approach, by comparing the cooperative's financial reporting practices with the standards set in SAK ETAP. Data collection techniques include interviews with the financial department and documentation studies of financial statements. The results indicate that KSP XYZ has only prepared two main financial statement components, namely the Balance Sheet and Income Statement, out of the five components required by SAK ETAP. The cooperative has not yet prepared the Statement of Changes in Equity, Cash Flow Statement, and Notes to the Financial Statements. Although the presentation of the Balance Sheet and Income Statement substantially complies with SAK ETAP, this incompleteness indicates that the implementation of SAK ETAP at KSP XYZ is not yet fully realized. This study recommends that management complete the preparation of financial statement components, digitize the accounting information system, and enhance human resource competence to improve the quality of financial reporting.